PEKERJA ANAK DI KOTA PEKANBARU (STUDI PADA ANAK-ANAK YANG BEKERJA SEBAGAI PEMULUNG DI KECAMATAN TAMPAN) - ", Seprianita; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study was conducted at Kecamatan Tampan. The purpose of this research is to analyze the distribution of income of child laborers as scavengers at Kecamatan Tampan Kota Pekanbaru. The focus of this research is the social and cultural conditions of child laborers as scavengers at Kecamatan Tampan Kota Pekanbaru. The technique of determining samples by Snowball Sampling and setting the number of subject as many as 10 people. The author uses qualitative descriptive method and Instrument data is observation, interview and documentation.Research conducted, the authors found that the social and cultural conditions of child laborers as scavengers at Kecamatan Tampan Kota Pekanbaru are: State Family Child Labor, children who work as scavengers come from poor families. Child Labor, most of the children who work as scavengers, are children who are ostracized from their peers. The Workplace Child Labor Environment, most of them live in very modest homes. The Everyday Activities of Child Labor, the child who works as their scavenger collects used goods for a long period of time in a day, they work over 4 hours a day. The Education of Child Labor, most of the children who work as scavengers, are children who are in school age. Distribution of child labor income as scavengers in Kecamatan Tampan Pekanbaru City is: All Revenues For Parents, most of the income earned from scavenging is handed or handled by parents. Revenue Shares With Two Parents, some of the proceeds from the sale of second-hand goods are shared for two with his parents.Keywords: Children, Workers, Scavengers, Economy